Saving an octocoral genus from a “zoanthid” genus: reversal of precedence of Palythoe Lamouroux, 1812, and Muricea Lamouroux, 1821 (Cnidaria: Anthozoa: Octocorallia) - Low, Martyn E. Y.; Reimer, James Davis (Zootaxa, 2011)
Lamouroux (1812: 360) established the genus-group name Palythoe, with the following diagnosis in French: “Palythoe […] P[olypiers] dendroïde rameux; axe presque toujours comprimé, recouvert d’une écorce trèsépaisse, en partie calcaire, parseméc de mammelous saillans, chacun terminé par une cellule polypifère”. This translates as: “A group dendroid in branching; almost always axially compressed, covered with very thick ectoderm, partly calcareous dotted with prominent bumps, each terminated by a polyp”.